DEVELOPMENT OF AN INSTRUMENT FOR ASSESSMENT OF THE IMPLEMENTATION OF BASIC TEACHING SKILLS FOR MATHEMATICS TEACHERS - Wilibaldus Bhoke; Melkior Wewe; Maria Carmelita Tali Wangge; Hilarion Jogo (Universitas Negeri Makassar, 2023)
This study aims to produce an instrument for assessing the implementation of teaching skills of Mathematics Teachers in cluster 5 of Boawae sub-district. This research is classified into the type of research & development (R&D). Data collection techniques using questionnaire and interview methods. All data that has been obtained is analyzed descriptively qualitative. The subjects in this study were teachers in cluster 5 of Boawae sub-district totalling 6 people. The outputs of this research are (1) An assessment instrument is produced in the form of an instrument of eight basic teaching skills for teachers in schools, (2) Based on the expert test related to the assessment instrument that has been developed, it meets the valid and practical criteria.